BRIDGING VOICES: SOCIAL VISION AND CULTURAL CRITIQUE IN THE WORKS OF RUSKIN BOND AND VIJAYDAN DETHA - Vaishnav, Ravi; Devi, Suman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research studies the works of notable indian authors Vijaydan Detha and Ruskin Bond. Despite writing in different languages and contexts their writing has similar qualities. Since Detha’s a local author, his works often appear to be an imitation of basic stories’s atmosphere with a modern twist to tell problems more fomalized that has national resemblance. His reimagination of folklore keeps it alive but makes it an area to fight back and rebuild. These two famous writers cite differant informations about where they feel the happiest at. His cut works make life seem less lifeless and human, some having a strong earthy twist. Bond is seen as a complex man who understands the fragility as well as the beauty of mountain life. The movie teaches how to live in the world, but inspires to raise above the world. When we have noble characteristics, we sometimes acquire other characteristics that we don’t want to desire having. The narrator connects ideas from postcolonial arguments and option studies with antropological information to show how authors get attached to damaged voices and omissions of reality through their writings. Detha’s folktales show people who are oppressed how to overcome their oppression. Similarly, Bond’s writings show humans can relate differently with nature. They create links that connect the local with the global, written word with the oral, and tradition with modernity. They make literary works which serve as a powerful moral force by creating a spectacular space in literature. Through this comparison, a greater understanding of India’s diverse cultures hopefully comes in future discussions. Most importantly, these texts reveal the power of fiction to act as always revealing our choices and behaviours.